Perspektif Rotasi Audit Dan Kualitas Audit Ditinjau Dari Mitra Audit Dan Perusahaan Audit - Muchamad Syafruddi; Faza Zanuba Khofsoh; Haryani Haryani (Akuntansi, 2024)
The function of auditing on reporting the financial condition of clients is vital. Therefore, a sustainable improvement on the contribution of successor and predecessor auditors during succession must not be ignored. This study aimed to investigate the connection between audit rotations and the quality of financial report, which is believed to be influential to the function of auditing. Research in this study was conducted using a multivariate regression analysis on the population of manufacturing companies listed in the Indonesia Stock Exchange from the year 2018 to 2022. By applying purposive sampling, 130 samples were selected. The total cumulative of audit firm rotations showed a positive coefficient, which indicated that audit firm rotations had a negative impact on increasing audit quality. The decline in quality of auditing was influenced by ineffective communication between predecessor and successor auditors which resulted in a pseudo-audit firm rotation.